Institutional features of wage bargaining in 23 European countries, the US and Japan - Philip Du Caju; Erwan Gautier; Daphne Momferatou; Melanie Ward-Warmedinger (European Central Bank (ECB), 2008)
This paper presents information on wage bargaining institutions, collected using a standardised questionnaire. Our data provide information from 1995 and 2006, for four sectors of activity and the aggregate economy, considering 23 European countries, plus the US and Japan. Main findings include a high degree of regulation in wage setting in most countries. Although union membership is low in many countries, union coverage is high and almost all countries also have some form of national minimum wage. Most countries negotiate wages on several levels, the sectoral level still being the most dominant, with an increasingly important role for bargaining at the firm level. The average length of collective bargaining agreements is found to lie between one and three years. Most agreements are strongly driven by developments in prices and eleven countries have some form of indexation mechanism which affects wages. Cluster analysis identifies three country groupings of wage-setting institutions.
Keywords: J31; J38; J51; J58; 330; cluster analysis; indexation; institutions; trade union membership; wage bargaining; Tarifverhandlungen; Institutionelle Infrastruktur; Lohnindexierung; Tarifvertrag; Dauer; Gewerkschaftsmitgliedschaft; EU-Staaten; Japan; USA